PENDEKATAN STEM SEBAGAI INOVASI PEMBELAJARAN PENDIDIKAN PANCASILA - Sari, Idas Agustianti; Mahluddin; Ahmad Sayuti Nainggolan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Pancasila Education learning in elementary schools still faces challenges in developing students’ creativity optimally. One effort that can be undertaken is the implementation of innovative and integrated learning approaches. This article aims to examine the application of the STEM (Science, Technology, Engineering, and Mathematics) approach as a learning innovation in Pancasila Education and its impact on enhancing students’ creativity. This study employed Classroom Action Research conducted in two cycles involving sixth-grade students of Madrasah Ibtidaiyah Nurul Yaqin Simpang Sungai Duren. Students’ creativity was analyzed based on indicators of fluency, flexibility, originality, elaboration, and redefinition. Research data were collected through observation, questionnaires, interviews, and documentation. The results indicate that the STEM approach was able to gradually improve students’ creativity. Students’ creativity increased from the less creative category at the initial stage to the fairly creative category in the first cycle and reached the creative category in the second cycle. The implementation of the STEM approach encouraged students to actively engage in learning activities, express ideas, collaborate with peers, and solve problems contextually. These findings confirm that the STEM approach can be used as an alternative learning innovation in Pancasila Education to enhance students’ creativity at the elementary school level.